Neo-Nazis in Toronto: The Allan Gardens Riot - Bialystok, Franklin (Canadian Jewish Studies / Études juives canadiennes, 1997)
In the early 1960s, after fifteen years of relative quietude,Canadian Jews once again came under attack by antisemites.Unlike the interwar years, when antisemitism leached downfrom some politicians and bureaucrats to society in general, thisnew strain was propagated by a tiny group of self-styled neo-Nazis. It was most virulent in Toronto. The Jewish communitythere was divided over how to respond. Traditional leadersstressed law and order, while others, led by a few militant survivors,demanded exposure and confrontation. Matters reacheda head with a riot that erupted in Allan Gardens when the leaderof the neo-Nazis attempted to hold a rally. In the ensuing weeks,the gap in the community widened. Consequently, as part of thehealing process, survivors were grudgingly accepted into corridorsof power in the Jewish community. For this reason, the riotwas the seminal event in the post-war history of the community.